Drenched in light eaudiobook - Wingate, Lisa (Tending Roses, 2019)
Once a gifted ballet dancer, Julia Costell buckled under the demands of a professional dance career, and has landed with a thud in an unglamorous job as a guidance counselor at a performing arts high school. Living back home with her parents and feeling lost, she is afraid she’ll never soar again…until the day young Dell Jordan is sent to her office, carrying an essay. In Dell’s writing, Julia sees luminous sparks of hope. But as she fights to forge a brighter future for one disadvantaged student, she is drawn into startling undercurrents of conflict and denial within the academy. Only when she is tested in ways she never could have imagined does she begin to discover where real meaning and fulfillment lie—and realize that even though her life has seemed off course, she’s been on the right path all along.